Phenotype of VCP Mutations in Chinese Amyotrophic Lateral Sclerosis Patients - Feng, Shu-Yan; Lin, Han; Che, Chun-Hui; Huang, Hua-Pin; Liu, Chang-Yun; Zou, Zhang-Yu (Frontiers in Neurology, 2022)
Mutations in the Valosin-containing protein (VCP) gene have been linked to amyotrophic lateral sclerosis in the Caucasian populations. However, the phenotype of VCP mutations in Chinese ALS patients remains unclear. Targeted next-generation sequencing covered 28 ALS related genes including the VCP gene was undertaken to screen in a Chinese cohort of 275 sporadic ALS cases and 15 familial ALS pedigrees. An extensive literature review was performed to identify all patients with ALS carrying VCP mutations previously reported. The clinical characteristics and genetic features of ALS patients with VCP mutations were reviewed. One known p.R155C mutation in the VCP gene was detected in two siblings from a familial ALS pedigree and two sporadic individuals. The same VCP p.R155C mutation was also detected in an additional ALS patient referred in 2021. Three patients with VCP p.R155C mutation presented with muscular weakness starting from proximal extremities to distal extremities. The other patient developed a phenotype of Paget’s disease of bone in addition to progressive muscular atrophy. We reported the first VCP mutation carrier manifesting ALS with Paget’s disease of bone in the Chinese population. Our findings expand the phenotypic spectrum of the VCP mutations in Chinese ALS patients and suggest that ALS patients with VCP p.R155C mutations tend to present with relatively young onset, symmetrical involvement of proximal muscles weakness of arms or legs, and then progressed to distal muscles of limbs.